2013
DOI: 10.1007/s00167-013-2454-7
|View full text |Cite
|
Sign up to set email alerts
|

Graft hypertrophy of matrix-based autologous chondrocyte implantation: a two-year follow-up study of NOVOCART 3D implantation in the knee

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 34 publications
1
52
0
Order By: Relevance
“…It is worth noting that graft hypertrophy can occur with second-and third-generation ACI. Niethammer et al 30 reported graft hypertrophy on magnetic resonance imaging (MRI) in 11 of 44 patients who had MACI (with Novocart -TETEC AG, B. Braun, Reutlingen, Germany).…”
Section: Lavage and Debridementmentioning
confidence: 99%
“…It is worth noting that graft hypertrophy can occur with second-and third-generation ACI. Niethammer et al 30 reported graft hypertrophy on magnetic resonance imaging (MRI) in 11 of 44 patients who had MACI (with Novocart -TETEC AG, B. Braun, Reutlingen, Germany).…”
Section: Lavage and Debridementmentioning
confidence: 99%
“…While Niethammer et al 22 observed no correlation between age or BMI with the development of graft hypertrophy, an association between younger patients and a higher incidence of hypertrophy has been observed after periosteal-covered ACI. 16 The origin of the cartilage defect may also play a role, 22 while it has been suggested that graft hypertrophy may have a cellular origin. 13 Henderson et al 13 noted an increased rate of graft hypertrophy in small-sized repairs with periosteal-covered ACI and proposed that the increased cell density in a smaller repair may lead to increased cellularity and matrix deposition within the repair.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2 years prospective MRI study, incomplete graft filling as assessed by MRI was common (55.7%) at 2 years and did not correlate with clinical results; the authors noted that graft thickness appeared to increase throughout the 2 years follow-up period [41]. A 2 years follow-up MRI study showed a 25% graph hypertrophy rate in Novocart 3D patients (11/44 patients), with higher hypertrophy rates in cases of acute traumatic defects or osteochondritis dissecans [42].…”
Section: Novocart 3dmentioning
confidence: 96%